2014
DOI: 10.1111/jam.12516
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial community dynamics during the early stages of biofilm formation in a chlorinated experimental drinking water distribution system: implications for drinking water discolouration

Abstract: AimsTo characterize bacterial communities during the early stages of biofilm formation and their role in water discolouration in a fully representative, chlorinated, experimental drinking water distribution systems (DWDS).Methods and ResultsBiofilm development was monitored in an experimental DWDS over 28 days; subsequently the system was disturbed by raising hydraulic conditions to simulate pipe burst, cleaning or other system conditions. Biofilm cell cover was monitored by fluorescent microscopy and a finger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
53
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(56 citation statements)
references
References 57 publications
3
53
0
Order By: Relevance
“…Thus, a relative abundance of a strain at 1% is considered to be a low abundance in a mixed population. Also, Methylobacterium species have been found to be present in drinking water in the United Kingdom [46,47] but they have not been found to be abundant in Glasgow tap water [40]. Here, only the case in which Methylobacterium was inoculated at the lowest relative abundance of 1% is reported.…”
Section: Inoculation Of Methylobacterium Into Drinking Watermentioning
confidence: 81%
“…Thus, a relative abundance of a strain at 1% is considered to be a low abundance in a mixed population. Also, Methylobacterium species have been found to be present in drinking water in the United Kingdom [46,47] but they have not been found to be abundant in Glasgow tap water [40]. Here, only the case in which Methylobacterium was inoculated at the lowest relative abundance of 1% is reported.…”
Section: Inoculation Of Methylobacterium Into Drinking Watermentioning
confidence: 81%
“…The formation and growth of biofilm may be affected by factors such as temperature, pH, nutrient availability on the substrate, or time (Else et al 2003; Moghadam and Zimmer 2014; Rinaudi et al 2006). The growth of biofilm is characterized by an initial rapid proliferation of microbial cells and increased microbial richness and diversity, which finally leads to the formation of a stable climax community (Davey and O’toole 2000; Douterelo et al 2014). Microbial colonization of plant material also affects detritivore performance.…”
Section: Introductionmentioning
confidence: 99%
“…A notable exception is the study by Salehi and colleagues 34 , where they monitored changes in water chemistry and bacterial growth during the first days/weeks of building occupation. Also, a study by Douterelo and colleagues 47 , showed that specific bacteria are dominant during the initial colonization (7 – 28 d) of distribution pipe materials. The fact is, in current practice the owners/operators have effectively no control over the communities that colonize their building plumbing systems.…”
Section: Discussionmentioning
confidence: 99%